Assessing the information content of the Statement of Internal Control (SIC) of PLC's in Malaysia : a qualitative perspective / Masetah Ahmad Tarmizi - Ahmad Tarmizi, Masetah (2006)
This study is conducted because there is no specific format imposed on the Statement of Internal Control (SIC) and there is sufficient observation to implicate that some of the PLC's adopted the "cut and paste" process in the preparation of the SIC. Particularly, this study ailTIs to achieve four objectives, firstly; to develop an Internal Control framework, secondly; to assess the information content of Malaysian's SIC, thirdly; to analyze the trend of the information content score and fourthly; to rank companies based on the information content of their SIC. This study chose companies listed with the Second Board as the sample frame and used content analysis and EXCEL Microsoft Office to produce graphs and charts. The significance of this study is mainly the provision of a suitable internal control framework that could be used by PLC's when they prepare the SIC. Secondly, these studies aim to recognize the information to be included within the SIC. Through analysis, this study found that PLC's provided more information on the control structure and environment with an average score exceeding 60% for all the years under reviews. This is followed by the information on risk ITIanagelTIent framework, objectives of the company to maintain a sound internal control system and roles & responsibilities the BOD, Audit committee and Internal Audit departlnent